THREE NEW SPECIES OF PTEROMALIDAE (HYMENOPTERA) FROM KERALA (INDIA) - NARENDRAN, T. C.; ., KRAJMOHANA; JOBIRAJ, T. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2001)
<span style="color: #000000; font-family: Roboto, sans-serif; font-size: 13px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Three new species of Pteromalidae viz. Kamarele semndiri Narendran & Mohana sp. nov., Callitula bambusae Narendran & Jobiraj sp. nov. and C poeetilinapada Narendran & Mohana sp. nov. are described and their affinities discussed with related species.